Joint Throughput Optimization for Multichannel Multiradio Multirate Wireless Network with Network Coding - Choi, G.; Yoon, W. (IETE Journal of Research, 2019)
Network coding has been proposed to increase network throughput by combining packets at intermediate nodes. In this paper, we propose a joint throughput optimization method for a multirate multichannel multiradio wireless network with network coding. We propose algorithms for congestion control, joint distributed rate control, and heuristic resource allocation to solve the utility maximization problem in the wireless network environment with network coding. To minimize performance degradation generated by packet loss, we propose a congestion control algorithm. Furthermore, we present a sophisticated resource allocation algorithm which finds a node for the worst traffic jam and selects a session that needs to be first transferred in the node. Then, the node is allocated with the channels and radios for the packets of the selected session. Furthermore, a rate selection method is presented to determine the rate of each node. The simulation results show that the proposed method achieves the optimal performance in a multirate multichannel multiradio wireless network.
Keywords: Multi-radio; Multi-radio wireless network; Multirate wireless networks; Rate controls; Resource allocation algorithms; Throughput optimization; Utility maximizations; Wireless network environment; Multichannel multiradio multirate; network coding; rate control; resource allocation; throughput optimization; utility maximization